Experience and management of two paediatric patients infected with SARS-CoV-2 with major burn injuries in an intensive care unit - Bustamante, Atenas (2020)
SARS-CoV-2 infection is rapidly disseminating, leading to a world pandemics in which we are also affected. In San Borja Peruvian National Children Health Institute, which is the reference center for surgical pediatric patients, 106 patients infected with SARS-CoV-2 were hospitalized. Of them, 11 presented with burns and two had large burns. The viral infection was diagnosed using molecular testing. We present in detail the case of a pediatric seven-year old patient who had large burns and was taken care of in the intensive care unit. She had asymptomatic SARS-CoV-2 infection, and her outcome was good, with a good prognosis, and she recovered completely and uneventfully. On the other hand, COVID-19 may present as a severe disease leading to a multisystemic inflammatory syndrome with some uncommon clinical manifestations which affect its prognosis , as it was the case with another seven-month old patient who passed away in spite of having received specialized and timely therapy.